Experimental measurement of the diamond nucleation landscape reveals classical and nonclassical features - Gebbie, Matthew A; Ishiwata, Hitoshi; McQuade, Patrick J; Petrak, Vaclav; Taylor, Andrew; Freiwald, Christopher; Dahl, Jeremy E; Carlson, Robert M K; Fokin, Andrey A; Schreiner, Peter R; Shen, Zhi-Xun; Nesladek, Milos; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2018)
Nucleation is a core scientific concept that describes the formation of new phases and materials. While classical nucleation theory is applied across wide-ranging fields, nucleation energy landscapes have never been directly measured at the atomic level, and experiments suggest that nucleation rates often greatly exceed the predictions of classical nucleation theory. Multistep nucleation via metastable states could explain unexpectedly rapid nucleation in many contexts, yet experimental energy landscapes supporting such mechanisms are scarce, particularly at nanoscale dimensions. In this work, we measured the nucleation energy landscape of diamond during chemical vapor deposition, using a series of diamondoid molecules as atomically defined protonuclei. We find that 26-carbon atom clusters, which do not contain a single bulk atom, are postcritical nuclei and measure the nucleation barrier to be more than four orders of magnitude smaller than prior bulk estimations. These data support both classical and nonclassical concepts for multistep nucleation and growth during the gas-phase synthesis of diamond and other semiconductors. More broadly, these measurements provide experimental evidence that agrees with recent conceptual proposals of multistep nucleation pathways with metastable molecular precursors in diverse processes, ranging from cloud formation to protein crystallization, and nanoparticle synthesis.
Keywords: thermodynamics; nanomaterials; diamond; nucleation; plasma synthesis